Rhabdochona hospeti Thapar, 1950: A Natural Parasite in Tor putitora - Joshi, Yagya Raj; Joshi, Promod (Far Western Review, 2024)
Rhabdochona Railliet, 1916 is a predominant intestinal parasite in fresh water fish all over the world. This study, aimed to investigate the infection level (prevalence, mean intensity and abundance) of nematode Rhabdochona hospeti Thapar, 1950 in golden mahseer (Tor putitora) in Mahakali River, Nepal, was conducted from September 2022 to August 2023. A total of 146golden mahseerwere collected from the two sites of the Mahakali River by using gill nets. Nematode parasites were retrieved and processed using standard helminthological methods. All sized and both male and female fish were found infected year-round. Overall, the prevalence, mean intensity and abundance of the Rhabdochona hospeti in golden mahseer were 90.41%,7.48and 6.77 respectively. Butthere was 100% prevalence in more than 150 gm weight fish in the months of September, January, February and April. The parasitic burden (mean intensity and abundance) was higher in more than 20 cm sized (8.29 and 7.48) female host fish (8.45 and 7.89) in the months of October (15.5 and 13.29) and autumn season (10.84 and 10.05). Statistically, the prevalence, mean intensity and abundance of the Rhabdochona hospeti were insignificant (p ˃ 0.05) with the body size and sex of the host fish, months and season of the year. This study reveals stable high infection of the Rhabdochona hospetias a natural parasite in golden mahseer fish in new locality and will be the one of the natural cause of fish decline from the river in near future.